ATG5 gene regulates testosterone synthesis of testicular Leydig cells in Hezuo pig - Du, Hong; Yan, Zunqiang; Shi, Haixia; Gun, Shuangbao (Frontiers in Veterinary Science, 2025)
Autophagy-related gene 5 (ATG5) plays a crucial role in autophagosome formation. Recent studies have investigated the role of autophagy in regulating testosterone production; however, its expression in testicular tissues and Leydig cells of Hezuo pig remains less understood. In this study, we cloned the coding sequence (CDS) region of the ATG5 gene and assessed its expression using qPCR across various tissues and testes at different developmental stages in Hezuo pigs. Subsequently, we constructed silencing and overexpression vectors for ATG5 and transfected them into Leydig cells. Cell proliferation and apoptosis were evaluated using CCK-8 and flow cytometry assays, respectively. Autophagy and testosterone synthesized gene expression were detected by qPCR, while ATG5, StAR and LC3 protein levels were measured by Western blotting. Furthermore, testosterone concentration and the levels of autophagy-related genes BECN1 (Beclin1), NPC1L1 (Niemann-Pick C1-like 1), and TSPO (translocator protein) were quantified via ELISA. The results indicated that the CDS region of the ATG5 gene spans 828 base pairs, encoding 275 amino acids. ATG5 showed high expression in the testis and lung (p < 0.01), with significantly higher expression in the testicular tissues of the 4-month-old group compared to the 1-month-old group (p < 0.01). Compared to the empty vector control (ATG5-PC), the overexpression group (ATG5-OE) exhibited increased cell proliferation (p < 0.05), reduced apoptosis (p < 0.01), elevated autophagy gene expression (BECN1, ATG7, and LC3) (p < 0.01) and testosterone synthesis-related genes (StAR, HSD3B and CYP11A1) (p < 0.01), along with increased ATG5, StAR and LC3protein levels (p < 0.01), as well as significantly increased testosterone levels, BECN1, NPC1L1, and TSPO expression (all p < 0.01). These findings indicate that ATG5 manipulation affects testosterone synthesis in Leydig cells, likely through autophagy regulation. This study offers novel insights into the function of ATG5 in testosterone production within testicular Leydig cells, providing theoretical support for investigating early puberty in Hezuo pigs.